Membina Kecemerlangan Kepimpinan dan Kerjasama Berpasukan dalam Taekwondo CNC - Iman Permana; Ana Tasyia Wulandari; Kirsten Helena Judith Sihombing; Vionisa Yoliandri; Sinta Rida Anabela; Suci Ramadhani; Elsha Daimora Ginting; Ghina Nafsi Amira; Nabil Fathur Rahman (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study focuses on the development of leadership qualities and teamwork among CNC Taekwondo players through organized training sessions at the President University Student Housing. A quasi-experiment was used to explore this study. Participants numbered 25, who were evaluated using pre-test, quiz, and post-test techniques. This training course made use of theoretical lectures, maze drawing teamwork games, as well as reflection sessions. Analysis of the pre-test revealed that the average percentage of correct answers is 84.8%, with the best scores for supportive guiding (96%) and honest communication practices (96%). Analysis of the quiz revealed that there is 91.7% understanding of leadership positions, as well as 100% understanding of integrity as a crucial foundation for trust development. Post-test analysis revealed that the average percentage of excellence for activity-based learning is 69.2%, while that of instructor comments is 61.5%. It is shown that the combination of scenario or learning activities with teamwork games is an effective tool for developing leadership qualities and teamwork with qualities of sportsmanship, discipline, responsibility, and spirit of teamwork among young Taekwondo players.